ChemInform Abstract: Catalytic Application of Zwitterionic Palladium Complexes in Mizoroki—Heck Reactions Using Ionic Liquid as Solvent. Issue 49 (December 2015) - Wang, Yi‐Ping; Lee, Hon Man
Abstract: Zwitterionic NHC‐type Pd‐complexes are synthesized, which efficiently catalyze Mizoroki—Heck reactions in ionic liquids.